Seasonal Influence on the Impact of Human Chorionic Gonadotropin (hCG) on Testicular Haemodynamics and Hormonal Responses in Canines: A Comparative Study - Behnam Nadali; Arman Abdous; Nima Karami; Mohammad Jokar; Ourang Ataie Amarloie; Mehran Farhoodi (Veterinary Medicine and Science)
ABSTRACT Human chorionic gonadotropin (hCG) is widely used to treat reproductive dysfunction by enhancing testicular blood flow and stimulating hormonal activity. This study investigates the seasonal variations in the response to hCG treatment in male dogs, focusing on its effects on testicular blood flow and plasma concentrations of testosterone and oestrogen. Conducted across different seasons (spring, summer, fall and winter), the study utilised colour Doppler ultrasonography to measure testicular haemodynamics and analysed hormonal levels at multiple time points post‐hCG injection. The findings revealed that the response to hCG is modulated by seasonal factors, with significant variations in both blood flow and hormone levels. A significant negative relationship was indicated between testicular blood flow and testosterone levels, particularly during spring and summer. These results suggest that seasonality should be considered when administering hCG for reproductive treatments in canines.